Determination of Total Protein Concentration in Solution Using Gold Electrode Modified with Silver Nanoparticles. Issue 1 (11th December 2014) - Tchekwagep, Patrick Marcel Seumo; Nanseu‐Njiki, Charles Péguy; Ngameni, Emmanuel; Danielsson, Ravi; Arnebrant, Thomas; Ruzgas, Tautgirdas; Gorton, Lo
Abstract Gold electrodes were modified with silver nanoparticles and Ag/AgCl redox conversion was recorded by cyclic voltammetry in protein containing electrolyte solution. The charge of the reduction peak decreased with the increase of the total protein concentration. This correlation was better for solutions containing bovine serum albumin as a standard than for the samples of human saliva. The results of these electroanalytical measurements show that the method can be used to determine protein concentration in electrolyte solution in the range from 0.01 to 0.2 mg mL−1, though reproducibility of analysis of real samples must be further improved.